Rancang Bangun Sistem Layanan Pengaduan Konsumen Berbasis Web - Sandi Lukman Nurhakim; Parman Suparman; Pardo Frans (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
Complaints are complaints submitted by users or customers to service providers or services that do not comply with service standards, or neglect of obligations and violations of prohibitions. In the process of processing service data regarding customer complaints, it is known that complaints are made by customers by sending complaint information via social media or via telephone contact. After the complaint information has been provided, the service department will inform the admin staff via WhatsApp media by sending complaint data and customer complaints. Then the company will contact the customer via telephone to confirm the complaint sent, If the complaint has been processed to completion then proof of completion in the form of a photo is sent back to the admin staff to be re-data. The method used in this research is Waterfall. This method is a systematic and sequential information system development model. The result of this research is to design and build a Complaint Service System PT. Mandiri Transforma Global Web-based to facilitate the processing of service data regarding complaints by customers, speed up information related to complaint services, speed up the process of making complaint service reports by company customers, both those that have been processed and those that have not been processed and can be accessed online.